Analysis of the Cytokine Expression in the Aqueous Humor of Individuals with BRVO-Associated Macular Edema - Chengyi Zhu; Lanlan Pan; Qiong Yi; Qiping Wei (Journal of Ophthalmology)
Purpose. This study aimed to determine the expression levels of vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) in the aqueous humor of patients with macular edema (ME) caused by branch retinal vein occlusion (BRVO), as well as to investigate the relationship between the cytokines as mentioned earlier and best-corrected visual acuity (BCVA), ME, and the degree of ME from the molecular level. Methods. In a prospective observational study, fluorescein fundus angiography (FFA) and optical coherence tomography (OCT) were used to classify 58 patients with non-ischemic BRVO-ME into three groups according to the degree of ME: 14-mild, 17-moderate, and 27-severe. The specific concentration of IL-6, VEGF, ICAM-1, and VCAM-1 in the aqueous humor was detected using the BD CSCanto™ II Flow Cytometer (US). Spearman or Pearson correlation analysis was used to test the correlation between the levels of BCVA and severity of ME and the expression levels of IL-6, VEGF, ICAM-1, and VCAM-1 in the aqueous humor. Results. According to the obtained data, BCVA did not correlate with the severity of ME, and these four cytokines expression levels in patients’ aqueous humor (P>0.05). Moreover, BCVA did not correlate with mild, moderate, or severe ME as well (P>0.05). However, the levels of these four cytokines were correlated with the severity of the ME. These underlined cytokines were linked to the mild, moderate, and severe degrees of ME. VEGF was also significantly correlated (r > 0.8, P<0.0001) with the severity of ME. Conclusions. This study suggests that the severity of ME in BRVO-ME patients is significantly correlated with the expression levels of IL-6, VEGF, ICAM-1, and VCAM-1 in the aqueous humor. Lowering the level of disease-associated cytokines may potentially reduce the degree of ME. Therefore, an in-depth study of the levels and the relationship may provide some evidence for the pathogenesis, treatment, and prevention of BRVO-ME.